Lactobacillus paracasei PS23 dietary supplementation alleviates muscle aging via ghrelin stimulation in d-galactose-induced aging mice. (October 2021) - Cheng, Li-Hao; Cheng, Shih-Hsuan; Wu, Chien-Chen; Huang, Chin-Lin; Wen, Pei-Jun; Chang, Min-Yu; Tsai, Ying-Chieh
Graphical abstract: Highlights: Lactobacillus paracasei PS23 (PS23) alleviates skeletal muscle atrophy in aging mice. PS23 restores ghrelin levels in d -galactose-induced aging mice. Ghrelin secretion in gastric cells is directly induced by PS23. PS23 is a potential anti-aging dietary supplement that delays muscle aging. Abstract: Some probiotics have been shown to alleviate age-related muscle atrophy via the gut-muscle axis. The aim of this study was to investigate the effects of live or heat-killed Lactobacillus paracasei PS23 (PS23) on muscle health in D-galactose-induced aging mice. Administration of D-galactose significantly reduced the strength, size, and levels of phosphorylated Akt in the muscle of mice. These effects were ameliorated by both live and heat-killed PS23 supplementation. Ghrelin is a multifaceted gut hormone with the ability to improve muscle atrophy. The levels of ghrelin in the serum and stomach of the aging mice were also significantly reduced and could be rescued by heat-killed but not live PS23. Furthermore, heat-killed PS23 greatly stimulated ghrelin secretion in the KATO III human gastric cell line. In conclusion, PS23 is a potential dietary supplement that can alleviate age-related muscle loss and dysfunction by regulating ghrelin secretion.